Korlátozott vezetői döntéshozatal, avagy a kockázati tőkés aktív szerepvállalása - Becsky-Nagy Patrícia (Taylor : gazdálkodás- és szervezéstudományi folyóirat, 2016)
Venture capitalists usually contribute to growth of their portfolio companies not only money but also their personal network and expert. This also means that they influence the management of the companies so they limit decision making. The article is looking for the answer how the limited managerial decision making and investors’ influence impact the whole company. The conclusion of the article is that limiting managerial decision making can reach its goal and result the growth of the company only in case the interests of shareholder and leaders are harmonised, so the principal-agent problem is bridged.